GESTÃO DE RESÍDUOS: UM ESTUDO DE CASO NO SETOR DE LOGÍSTICA REVERSA DA COMPANHIA ENERGÉTICA DE MINAS GERAIS - Ramos, Marco Aurélio; Maia, Sergio Geraldo; Melo, Alfredo Alves de Oliveira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
From a case study, performed at the Reverse Logistics Companhia Energetica de Minas Gerais (Cemig), this paper presents an approach on the subject of waste management. The research has developed to investigate the importance of waste management for the organization, from an inner vision, identified by means of document analysis and interviews with managers involved in the process studied. The information gathered in field research were analyzed in a qualitative manner. The studies showed, in general, the existence in the organization of a well structured management of waste, known internally as aggregating value to the business, especially in terms of the requirements of sustainability. However, we also identified some challenges in waste management, such as aspects related to compliance with the law and the requirements of different forms of action, given the great diversity of materials to be designed. It should be noted also that the activities within the context of the sector investigated, among them the management of waste does not include the return of goods to manufacturers / suppliers, showing an efficient process in principle, however, partially detached from the real concept of logistics reverse